TOWARDS ACHIEVING FUNCTIONAL ADULT LITERACY IN NIGERIA - Ayodele, Joseph Babatola; Adedokun, Mary Olufunke (European Scientific Journal, ESJ, 2012)
Education is not only a social service but a transformative act which is fundamental to social and personal development because when there is access to education, there is an increase in social and political awareness and heightened aspirations, self assurance and self assertiveness. The main role of education in man’s life is to expand people’s knowledge base thereby helping us to shape our destinies and move us towards desirable goals and better living. Based on this assumption, everybody in Nigeria should have a measure of literacy education and one that will make them functional in all they do with the result that economic benefits will accrue to them and thus making them to have an improved living. It is on this basis that everybody in the society should aspire to be literate. It is against this background that this paper examined how to realize the goal of functional adult literacy in Nigeria.